A Scenario-based Interval Multi-objective Mixed-integer Programming Model for a Water Supply Problem: An Integrated AHP Technique - Ucler, Nadire; Gonce Kocken, Hale (Water resources management, 2023)
Rapid population growth, industrialization, and lifestyle modernization all increase water demand. However, water supplies are dramatically decreasing due to declining and irregular precipitation and the excessive use and deterioration of existing resources. This situation places tremendous pressure on decision-makers, who must implement plans to create new water supplies in regions likely to experience water shortages in the future. Deciding which projects to implement among various alternatives is challenging with a limited budget. This study aims to create a feasible strategic plan to select the most suitable alternative projects by proposing a multi-objective mixed-integer programming approach to the water supply problem. Considering several criteria, including chance of success, ease of application, nature-friendliness, and project prestige level, the proposed model is integrated using the analytical hierarchical process technique. Decision-makers’ views of the project alternatives are reflected by weights in the model. Also, interval numbers represent the costs of alternatives to handle the problem more realistically. A real-life situation is simulated under various scenarios to test the proposed model. The results show that the proposed integrated model generates more applicable solutions than a classic multi-objective optimization model.